Qualitative Design in Political Communication Research, Surveys and Public Opinion - SIBANDA, Phathiwe; SIBANDA, Mabutho; PHESA, Masibulele (PT Keberlanjutan Strategis Indonesia, 2023)
The main aim of this study was to unpack the health and socioeconomic status of waste-picking activities in Mayville, Cato Manor, and Westville in Durban. It analyzed the quality of life of waste pickers, their awareness of the risks associated with this kind of work, and the extent of their uptake of health-protective measures. A quantitative approach was adopted, and a questionnaire was used to gather data from 81 waste pickers. The findings revealed that unemployment was the main reason for taking up waste picking and that this was the respondents' primary source of income. It was also found that most respondents resided in shacks and had no access to running water. Most were unaware of the risks associated with this kind of work. Based on these findings, it is recommended that economic development be pursued to create employment opportunities and that delivery of essential services such as potable water be improved, especially in informal settlements. Awareness campaigns should be launched to educate waste pickers on handling waste, the risks associated with this kind of work, and the need to adopt protective health measures. Finally, the researcher recommends further research on waste picking in Durban as there is a paucity of information on this activity in the city.